1993
DOI: 10.1037/0012-1649.29.4.739
|View full text |Cite
|
Sign up to set email alerts
|

Understanding person-space-map relations: Cartographic and developmental perspectives.

Abstract: Drawing from cognitive–developmental and cartographic theory, we tested children's understanding of person–map–space relations. After introducing maps of the classroom, an adult moved to different positions in the room and pointed straight ahead. Five– to 12-year-old children (N = 259) placed colored arrow stickers on the map to show the person's location and heading, once when the map was aligned with the room and once when rotated 180°. Performance was better on the aligned condition and when headings were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 30 publications
4
78
0
3
Order By: Relevance
“…Regarding the former, there is a growing body of cartographic research reported in the psychology literature on spatial concepts (e.g. Liben & Downs, 1993;Wiener, Hölscher, Büchner, & Konieczny, 2012) and spatial abilities (e.g. Hegarty, Montello, Richardson, Ishikawa, & Lovelace, 2006;Miyake, Friedman, Rettinger, Shah, & Hegarty, 2001).…”
Section: Psychologymentioning
confidence: 99%
“…Regarding the former, there is a growing body of cartographic research reported in the psychology literature on spatial concepts (e.g. Liben & Downs, 1993;Wiener, Hölscher, Büchner, & Konieczny, 2012) and spatial abilities (e.g. Hegarty, Montello, Richardson, Ishikawa, & Lovelace, 2006;Miyake, Friedman, Rettinger, Shah, & Hegarty, 2001).…”
Section: Psychologymentioning
confidence: 99%
“…However studies showed also challenges of using VGA to correlate visibility and locations in environment where orientation is performed. Orientation is an important step of using cognitive maps for route planning and executing in wayfinding behaviors [25]. Davies et al [24] tested using VGA and behavioral experiments to evaluate wayfinders' estimations of orientation.…”
Section: Visibility Graph Analysis (Vga)mentioning
confidence: 99%
“…Spatial cognitionstudies suggest that this difficulty may be due to conflict between the observer-centered and the allocentric viewpoints. For example, children's difficulty describing a scene from someone else's perspective is often associated with errors reflecting their own viewpoints (Liben & Downs, 1993;Rieser, Garing, & Young, 1994). Adults are not much different.…”
mentioning
confidence: 99%